2020
DOI: 10.1001/jamanetworkopen.2019.20548
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Best Practice Alert and Referral Process for Preprocedure Antithrombotic Medication Management for Patients Undergoing Gastrointestinal Endoscopic Procedures

Abstract: IMPORTANCE Management of antithrombotic medications presents a challenge for many clinicians and patients before procedures. Anticoagulation clinic involvement may improve preprocedure coordination, satisfaction on the part of patients and clinicians, last-minute procedure cancellations, and patient safety. OBJECTIVE To assess the implementation of an electronic medical record (EMR) best practice alert (BPA) and anticoagulation clinic referral process to assist with management of antithrombotic medication befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“… 21 As described previously, a diverse group of stakeholders was intimately involved in the development and pilot of this process. 12 While our system did require additional FTE pharmacist effort to handle the additional volume, we have previously shown that fewer cancellations resulting from this referral and review process would result in significant cost savings to the hospital system and would more than cover the additional costs. 12 …”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“… 21 As described previously, a diverse group of stakeholders was intimately involved in the development and pilot of this process. 12 While our system did require additional FTE pharmacist effort to handle the additional volume, we have previously shown that fewer cancellations resulting from this referral and review process would result in significant cost savings to the hospital system and would more than cover the additional costs. 12 …”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, other clinics that have explored this preprocedure management process have found it to be feasible 21 . As described previously, a diverse group of stakeholders was intimately involved in the development and pilot of this process 12 12 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations